The profile of “super-helpers”? Findings from the Generational Transmissions in Finland survey - Hämäläinen Hans; Tanskanen Antti O.; Danielsbacka Mirkka (Turun yliopisto, 2022)
This study considers “super-helpers,” namely older adults who help others in the private and public spheres. Although super-helpers can be important actors at individual, community, and social levels, only a few studies have evaluated their characteristics. We explored the profiles of super-helpers by drawing upon population-based data of older Finns (n = 2,174) and examined their provision of: 1) instrumental help (i.e., practical help or personal care) to friends and relatives; 2) financial aid to friends and relatives; and 3) public support (i.e., through volunteering or charitable giving). Of the respondents, 75% provided instrumental help, 44% provided financial aid, and 65% offered public support. Overall, 26% were considered super-helpers, that is, they were engaged in providing all three types of support. Having a partner, higher level of education, better perceived financial condition, being religious, and having a larger number of close relatives increased the probability of being a super-helper. The results are interpreted in light of opportunity structures and role extension approaches.